Parametric Study on Dynamic Characterization of Municipal Solid Waste Fine Fractions for Geotechnical Purpose - Rawat P.; Mohanty S. (My University, 2025)
The study focuses on the potential use of municipal solid waste (MSW) fine fractions, that is, fraction below 4.75 mm size for geotechnical applications (backfill/embankment material). In addition, the utilization of these MSW fine fractions in seismic-prone regions demand the dynamic characterization of the material under dynamic loading conditions before its application in the field. Hence, to check the influence of different parameters, that is, relative compaction, effective confining pressure, loading frequency, and strain amplitude on dynamic shear modulus (G) and damping ratio (D) of MSW fines, a set of 44 consolidated undrained cyclic triaxial tests (CTT) were performed. The investigation verifies that some parameters, such as relative compaction, effective confinement, and strain amplitude, have a more significant influence on the dynamic properties of the considered MSW fine fractions than do others, such as loading frequency. The results of this dynamic study can be successfully implemented using the considered MSW fine fractions as soil replacement. © 2021 American Society of Civil Engineers.